The hunter [videorecording (DVD)] - Kulik, Buzz; McQueen, Steve, 1930-1980; Wallach, Eli, 1915-2014; Harrold, Kathryn, 1950- (Paramount Home Entertainment ; Distributed by Warner Home Video, 2006)
The true story of Ralph "Papa" Thorson, a modern-day bounty hunter. Thorson pursues fugitives who have skipped bail. The chase comes full circle when he becomes the quarry of a vengeful psychopath.